Dilema Reformasi Struktural Polri: Menakar Keseimbangan Independensi dan Akuntabilitas di Bawah Presiden atau Kementerian - Edi Saputra Hasibuan (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2026)
The placement of the Indonesian National Police (Polri) within the constitutional structure—directly under the President or under a ministry—remains a contested issue in Indonesia’s security-sector reform amid a persistent deficit in public trust and human rights protection. This article analyses the direction of police reform and weighs the constitutional consequences of both placement options. Employing a juridical-normative method with statutory, conceptual, case, and comparative approaches, this study examines primary and secondary legal materials, including Constitutional Court Decision No. 19/PUU-XXIII/2025. The study finds that the dichotomy of ‘under the President versus under a ministry’ is a false binary: the quality of democratic policing depends not on the structural locus but on the design of institutional safeguards: namely, guaranteed operational independence of investigation, legally empowered external oversight, and transparency. Comparative evidence from the United Kingdom, Japan, and France shows that police placed under a ministry can remain professional and democratic when such safeguards exist. The article recommends retaining Polri under the President while reconstructing the National Police Commission (Kompolnas) from an advisory body into an oversight body with binding ethical-investigative authority through amendment of Law No. 2 of 2002.